Identification of susceptibility loci for Takayasu arteritis through a large multi-ancestral genome-wide association study - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (CELL PRESS, 2021)
Takayasu arteritis is a rare inflammatory disease of large arteries. We performed a genetic study in Takayasu arteritis comprising 6,670 individuals (1,226 affected individuals) from five different populations. We discovered HLA risk factors and four non-HLA susceptibility loci in VPS8, SVEP1, CFL2, and chr13q21 and reinforced IL12B, PTK2B, and chr21q22 as robust susceptibility loci shared across ancestries. Functional analysis proposed plausible underlying disease mechanisms and pinpointed ETS2 as a potential causal gene for chr21q22 association. We also identified >60 candidate loci with suggestive association (p < 5 x 10(-s)) and devised a genetic risk score for Takayasu arteritis. Takayasu arteritis was compared to hundreds of other traits, revealing the closest genetic relatedness to inflammatory bowel disease. Epigenetic patterns within risk loci suggest roles for monocytes and B cells in Takayasu arteritis. This work enhances understanding of the genetic basis and pathophysiology of Takayasu arteritis and provides clues for potential new therapeutic targets.
Keywords: GENETIC RISK; DISEASE; LEFLUNOMIDE; PSORIASIS; INTEGRIN; PROTEIN; CLASSIFICATION; ACTIVATION; CRITERIA; POLYDOM